PLACENTAL WEIGHT AND ANEMIA - M. Mirdamadi; M. Golshan; B. Aflaki; H. Nazemian; M. Salimi (Iranian Journal of Public Health, 1977)
A prospective study of 550 consecutive mothers delivered in Amin Ob. Gyn center of Isfahan University was performed to determine the relationships between maternal anemia, placental weight and neonatal birth weight. The important findings were marked placental hypertrophy in anemic mothers. (r= -/9.95) .It is probable that in anemic mothers placental hypertrophy is a compensatory mechanism responsible for an increase in fetal oxygen-uptake.